An unfolding monkeypox outbreak in Europe and beyond - Wallau, Gabriel Luz (2022)
Fundação Oswaldo Cruz. Instituto Aggeu Magalhães. Departamento de Entomologia and Núcleo de Bioinformática. Recife, PE, Brazil / National Reference Center for Tropical Infectious Diseases, Department of Arbo‑ virology, Bernhard Nocht Institute for Tropical Medicine, WHO Collaborating Center for Arbovirus and Hemorrhagic Fever Reference and Research, Hamburg, Germany.